2005
DOI: 10.1210/en.2004-1120
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Growth Hormone Receptor Knockout Mice: Interaction of Reduced Insulin-Like Growth Factor I/Insulin Signaling and Caloric Restriction

Abstract: Reduced IGF-I/insulin signaling and caloric restriction (CR) are known to extend the life span and delay age-related diseases. To address the interaction of these two interventions, we subjected normal (N) and long-lived GH receptor knockout (GHRKO) mice to CR for 20 months starting at weaning. We also used bovine GH transgenic (bGH Tg) mice, which overexpress GH and are short-lived and insulin resistant, for comparison. Circulating insulin and IGF-I levels were reduced by CR in N animals, whereas GHRKO animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 213 publications
(163 citation statements)
references
References 46 publications
12
149
2
Order By: Relevance
“…We have previously reported that this regimen of CR produces the expected reduction in body weight in both KO and normal mice (35). In the same study, CR down regulated circulating IGF1 levels in normal animals, while the extremely low levels of circulating IGF1 in both KO-AL and KO-CR animals were below the detection limits of the employed ELISA kit used in these studies (35).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…We have previously reported that this regimen of CR produces the expected reduction in body weight in both KO and normal mice (35). In the same study, CR down regulated circulating IGF1 levels in normal animals, while the extremely low levels of circulating IGF1 in both KO-AL and KO-CR animals were below the detection limits of the employed ELISA kit used in these studies (35).…”
Section: Discussionmentioning
confidence: 66%
“…The detailed protocol of the experiment was described previously (34,35). Because differences between genotypes and/or after CR treatment tend to be more pronounced in older animals, we continued caloric restriction for the period of 19 months till the animals reached the age of 21 months.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the mouse demonstrate that different dwarf mice, smaller than normal littermates by weight and characterized by decreased levels of IGF-1, live longer than littermates (Al-Regaiey et al 2005). The current study evaluated serum IGF-1 levels in dogs of highly variable size on the basis of body weight.…”
Section: Resultsmentioning
confidence: 98%